Fast computational processing for mobile robots' self-localization - Ribeiro, Helder (2016)
This paper intends to present a different approach to solve the Self-Localization problem regarding a RoboCup’s Middle Size League game, developed by MINHO team researchers. The method uses white field markings as key points, to compute the position with least error, creating an error-based graphic where the minimum corresponds to the real position, that are computed by comparing the key (line) points with a precomputed set of values for each position. This approach allows a very fast local and global localization calculation, allowing the global localization to be used more often, while driving the estimate to its real value. Differently from the majority of other teams in this league, it was important to come up with a new and improved method to solve the traditional slow Self-Localization problem.